Perspective of Farm Gate Agroforestry Product in the Emergency of the Chepangs Community: A Case Study of Mega earthquake of Central Nepal (International Journal of Scientific Research and Management (IJSRM), 2018)
Agroforestry is one of the major sources of sustenance among the people of Nepal, and only one mode of livelihood at the Chepangs in present days. National Seismological Centre (NSC-Nepal), recorded mega earthquake (7.8 Mw) that hit the country on the 25th of April in 2015, and many of its aftershocks had catastrophic effects. As a result, big structures collapsed, which incurred great losses on fabrication, collection centers, schools, markets, and other potential government, and private service centers. Continue aftershocks, and after two weeks later another earthquake hit (6.3 Mw) jeopardize Chepangs food security in Makwanpur. This study was designed to find out the food security, and market situation of agroforestry product of the Chepang community in Raksirang (One of the Severely affected VDC in Makwanpur district) due to the earthquake. A total of 40 households (12 %) were selected as a sample size. Questionnaires, Focus Groups Discussion (FGD), Observation, key informant interview tool were applied, and detail information from District Disaster Response Committee (DDRC), and emergency support agencies (UNICEF, WFP, PLAN, TEAR Fund) were consulted for additional narrative information. The research illustrated that approx. 370 hectares of land, with agroforestry plantation, ruptured by the earthquake, caused severe damages to the household’s structure, and a loss of food-stock up to 2/3 portion. Instead of regular cereal (rice, maize, and vegetables) intake, banana (Musa paradisiaca) consumption was in high scale during the emergency period. The market price of rice increased by 18.9 % due to demand. Income variation found before, and after the disaster. Prior to earthquake, agroforestry-livestock product was accelerating, but after the earthquake, agroforestry remains the only one means of livelihood among Chepangs. Nearly, half of agroforestry production of banana (Musa paradisiaca), citrus (Citrus lemon), pineapple (Ananus comosus) and broom grass (Thysanolaena maxima) declined, which was ready to harvest within 2-3 weeks. Heavy demands of agroforestry product above lay high farm gate prices (Up to doubled) helps surveyed community to continue livelihood from its sale. Nearly, 75 % respondents migrated to safe location due to land rupture, ongoing aftershocks, and occurring landslides. Overall food security situation in this community is acute, and challenging for the days to come. Immediate, and long-term response through relief agency concerning food, shelter, and safe stocking of agroforestry product is required. Agroforestry plantation and technical support to increase production, and to balance the food security and livelihood for longer period are the upcoming challenges in the coming days.